2008
DOI: 10.1007/s00380-008-1056-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of corrected QT dispersion with symptoms improvement in patients receiving cardiac resynchronization therapy

Abstract: Cardiac resynchronization therapy (CRT) is theoretically expected to affect repolarization as well as depolarization. We studied the effects of CRT on corrected QT (QTc) dispersion in association with symptomatic improvement. QTc dispersion was analyzed in 26 consecutive patients (67 +/- 6 years old, 18 men and 8 women) who underwent CRT. CRT responders and nonresponders were defined as patients showing and not showing > or = 1 class New York Heart Association symptomatic improvement 3 months after CRT, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
0
5
0
1
Order By: Relevance
“…Hina et al 23 showed that when we find the highest QTDc values before implantation of the resynchronization device (mean 102 ± 26 ms), patients are more likely to have a good response to CRT compared to nonresponders (mean 40 ± 12 ms), over a 3‐month follow‐up period. This type of analysis was not done in our study; however, we believe that this is a very elegant approach, considering that with simple data such as QTD values obtained by a reliable recording method, Hina et al were able to amass valuable information which can be used for prognosis and for further refining the indication for CRT.…”
Section: Discussionmentioning
confidence: 71%
“…Hina et al 23 showed that when we find the highest QTDc values before implantation of the resynchronization device (mean 102 ± 26 ms), patients are more likely to have a good response to CRT compared to nonresponders (mean 40 ± 12 ms), over a 3‐month follow‐up period. This type of analysis was not done in our study; however, we believe that this is a very elegant approach, considering that with simple data such as QTD values obtained by a reliable recording method, Hina et al were able to amass valuable information which can be used for prognosis and for further refining the indication for CRT.…”
Section: Discussionmentioning
confidence: 71%
“…1 and Table 1). In 3 of the 14 references, the data of endpoints were provided by subgroups (6, 14, 17). In 2 of the 14 references, the data was expressed as mean and standard error, the standard deviation was calculated (11, 15).…”
Section: Resultsmentioning
confidence: 99%
“…These findings were verified by another experimental study reported by Fish et al (23), which suggested that epicardial activation of left ventricular wall prolongs QT and TDR. However, results of following studies were inconsistent or even contradictory (7, 8, 14). Santangelo et al (7) reported that LV pacing enhanced QTD and TDR, whereas BV pacing significantly reduced QTD and TDR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A small study performed on 26 patients with CHF who underwent CRT showed that QTc dispersion is potentially useful for distinguishing CRT responders from CRT nonresponders before CRT 34 …”
Section: Discussionmentioning
confidence: 99%